The extension agent of the future - Jiménez, Daniel; Ortíz Crespo, Berta; Güereña, David T.; Davis, Kristin E.; Bennett, Gelsey (2021)
The Community of Practice in Data-Driven Agronomy (Big Data Platform – CGIAR) and the Feed the Future Developing Local Extension Capacity (DLEC) have joined forces to explore and define the future of agricultural extension far beyond sustainable crop production. The findings highlight the main knowledge, skills and attitudes that the Extension Agent of the Future should have.